Interlocking brick / Azri Zulhakim Ab Aziz - Ab Aziz, Azri Zulhakim (2021)
Interlocking bricks is used in Industrial Building System (IBS) which is blockwork system, one of the six categories of Industrialized Building System (IBS). Industrial Building System (IBS) is a term used in Malaysia. It refers to a construction technique in which components are manufactured in a controlled environment-either inside or outside the site where they are placed and installed for construction work.